INTERAKSI SOSIAL MASA RESES ANGGOTA DPRD DAPIL II KOTA PEKANBARU TAHUN 2015 - Almakshum, M Ridwan; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Samsul Bahri and Masny Ernawati are Members of DPRD Kota Pekanbaru from Dapil II (Kecamatan Rumbai and Kecamatan Rumbai Pesisir), who performed the recess period in 2015. Both Members of DPRD who were elected for the 2014-2019 period were very enthusiastic to accommodate people‟s aspirations that were going to be recommended for policy-making process in Kota Pekanbaru especially Kecamatan Rumbai and Kecamatan Rumbai Pesisir. Because, in the context of political sociology, politics is the process of shaping and division of power in people that, among others, presents as a process of decision-making, especially those concerning development of many aspects, such as infrastructure development, and education. The aim of this research is to analyse which desired people‟s aspirations were realised in the recess period at Dapil II Kota Pekanbaru and to analyse the implementations of aspirations gathered in said recess period. Theories (approaches) used as the instrument of analysis in this research is the theorem of political sociology, social interactions, and leadership, while the research method used is the method of qualitative research. Research results showed that the delivered aspirations were many and varied. Samsul Bahri, there were 64 proposals delivered in the recess period of 2015, 29 (45%) of those were proposals concerning infrastructure development, while Masny Ernawati, there were 73 proposals in the recess period and 37 of them are about infrastructure development, interestingly, from Masny Ernawaty‟s recess period, there were many proposals in the first recess that showed up in later recess. Concerning implementations of aspirations gathered in the recess period, Samsul Bahri as a Member of DPRD Kota Pekanbaru had implemented 13 aspirations of all proposals gathered in recess period, aside of supplying studying desks for SDN 93 Pekanbaru, Samsul Bahri had gone through the development of infrastructures ranging from development of 2 MDA learning rooms, provisioning of 2 hectares marketplace, 17 nodes of street lightings, to asphalting 2 roads totalling 1.550 metres in length, including drainage and culverts. Being only one year in office, Samsul Bahri was good enough in voicing people‟s aspirations. Masny Ernawati as a Member of DPRD Kota Pekanbaru had performed 9 activities from interactions with people in the recess, from those 9 varied activities, Masny Ernawati had gone through the development of 1.500 metres of concrete road in Teluk Leok, development of gutters totalling 150 metres in each side of Jalan Harapan, aside of 1 drilled water well and supplying 150 pairs of studying desks and chairs for SMKN 7 PekanbaruKeywords: Recess, Aspirations, Samsul Bahri, Masny Ernawati